Nutritional improvement of poultry feed by supplementation with protease-spent copra meal - Anglo, Pilar G.; Baens-Arcega, Luz; Arguelles, Angelina Ll (1982)
In feeding experiments on chicks, protease-spent copra meal or molded copra meal supplementation to the basal poultry feed has been found to enrich the nutritional value of the feed and to lower the mortality rate of the experimental chicks.